I once was a monkey : stories Buddha told - Lee, Jeanne M. (Farrar, Straus and Giroux, 1999)
A retelling of six Jatakas, or birth stories, which illustrate some of the central tenets of Buddha's teachings, such as compassion, honesty, and thinking clearly before acting.